Strategi Pengembangan Industri Kreatif Pariwisata Ramah Muslim Melalui SOAR Analysis dan Quantitative Strategic Planning Matrix (QSPM) - Moch Mahsun; Aunur Rofiq; Munawar Ismail (OECONOMICUS Journal of Economics, 2022)
Halal tourism is one part of the halal industry ecosystem, realizing a world halal hub in 2024. This research supports the presentation of a Muslim-friendly tourism industry, especially in encouraging the improvement of the creative economy (sharia) in Indonesia, which is still relatively increasing but not too significant. Even though Muslim-friendly (halal industry) is not visited only by the Muslim community. his research focuses on discussing halal tourism and sharia economic development strategies as a reference in realizing the halal creative industry in Indonesia. The research method uses SOAR (Strength, Opportunity, Aspirations, Result) and QSPM (Quantitative Strategic Planning Matrix) analysis to determine strategic priorities in realizing the halal industry in the Muslim-friendly tourism sector. The results of the QSPM analysis lead to the optimization of human resources specifically targeting Muslim-friendly tourism expertise through selection, socialization and workshops/training related to functions, the eco-system of halal tourism through the stages on the road maps of halal tourism in Indonesia. through a system that has been formed, the halal certification process is accelerated through mentoring, certification of halal auditors and supervisors so that the form of halal quality products can be guaranteed, with the highest score of 2,4926.